(Sobre)vivências das sexualidades: estudo antropológico em um hospital psiquiátrico de Maceió/AL - Santos, Jarissa Porto dos (2014)
This paper brings some reflections concerning the health professional perceptions about individuals who experience psychological distress in their emotional and sexual lives. The presented data are the result of ethnographic research conducted in a psychiatric hospital in the city of Maceió (Alagoas-Brasil) from December to July 2013, having as main interlocutors professionals that comprise the sectors of nursing, occupational therapy, social services, nutrition, psychology and psychiatrists. The study tried to create a dialogue with the information collect in the research field through the daily routines of the institution. One of the main aspects highlighted in this work is the stigma that leads the life of the people who were diagnosed with mental disorders, especially, considering the delegitimized place of the institutionalized bloke, in order to be subjugated, controlled and punished for their ‘disorders’. The research field data indicate the naturalized idea of abnormality, such that it becomes latent when it faces the emotional-sexual expressions of the blokes taken as’ crazy. Sexual practices are repressed (heterosexual, homosexual, masturbation) and pregnancy is prevented by physical containment mechanisms and managing medications. The hypersexuality, for example, is one of the categories activated when it’s thinking about the patient’s sexuality. The strategies frequently used involve infantilization or punishment through the Psychiatric Emergency, when patients insist on disobeying the rules. Adjectives ‘flirtatious’ or ‘flirt’ are most often used to refer to them, recognized from a ‘animalistic’ perspective of the sexuality. In turn, patients develop modalities of resistance against this existing controlling model, using the dark recesses of the hospital to meet up themselves. Thus, this research shows some elements that help us to problematize normative standards of sexuality, discussing how these prototypes interfere on a moral judgment of the manifestations that comes from blokes in psychological distress.